First-in-human trial of Stabilizer device in neuroendovascular therapy - Chiaki Sakai; Nobuyuki Sakai; Ariel Takayanagi; Hirotoshi Imamura; Tsuyoshi Ohta; Masaomi Koyanagi; Masanori Goto; Ryu Fukumitsu; Tadashi Sunohara; Nobuyuki Fukui; Shirabe Matsumoto; Tomoaki Akiyama; et al. (Heliyon, 2023)
Objectives: Flow diverter or stent implantation to intracranial target lesion requires large inner diameter microcatheter navigation. The exchange method using stiff long wire is often necessary if it is difficult to navigate over the regular guidewire. However, this method has an intrinsic risk of vessel damage and may cause severe complications. We investigated the safety and efficacy of a new device, the Stabilizer device for navigation in a first-in-human clinical trial under the Certified Review Board agreement. Materials and methods: The Stabilizer is a 320 cm length exchange wire with a stent for anchoring and is compatible with a 0.0165” microcatheter. The trial design is a prospective single-arm open-label registry. Inclusion criteria are elective flow diverter treatment or stent-assisted coiling, expected to be difficult to navigate a microcatheter with a regular micro guidewire, and obtained documented consent. The primary endpoint of the study was a hemorrhagic complication. Results: Five patients were enrolled in this trial. The median age is 52 years, ranges from 41 to 70, and all patients were female. Three aneurysms were located on the internal carotid artery, one on the vertebral artery, and one on the basilar artery. Basilar artery aneurysm was treated by stent-assisted coiling and others were treated by flow diverter deployment. All cases successfully navigate microcatheter for the treatment by the trial method using Stabilizer device without any adverse event. Conclusions: The results from this first-in-human consecutive five cases show the safety of the Stabilizer device in neuro-endovascular therapy for navigation of devices to the intracranial target lesion.